DESAIN PEMBELAJARAN BAHASA ARAB BERBASIS TEKNOLOGI INFORMASI DI ERA NEW NORMAL - Norkhafifah, Siti; Syahabuddin, Nur (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
In the midst of the pandemic that hit Indonesia, the direction of learning that used to be carried out face to face has now changed to learning that refers to technology and teaching and learning process activities are carried out from home. Thus, the design of Arabic learning has also changed for the continuity of education, information technology (IT) is needed as a solution. No wonder if during the pandemic the Arabic language learning design got a new formulation by paying attention to additional element, namely electronic (digital) media. This research was written using a qualitative method of literature study. Namely by collecting various data relevant to the topic discussed. Then analyzed and drawn conclusions. From this research, we get an overview of the main elements of Arabic learning design, namely in the form of determining goals, materials, strategies or media and evaluating them in the midst of a pandemic (new normal). The result of this research are important for educators to pay attention to when they want to carry out learning during a pandemic. As a material for consideration and guidance for educators in determining the design of Arabic learning.